STUDI EMPIRIS PERILAKU KEPATUHAN PAJAK PADA WAJIB PAJAK ORANG PRIBADI (STUDI PADA KPP PARATAMA PAMEKASAN) - Astri Furqani; Norsain Norsain (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
Tax compliance issue is a classic problem encountered in almost all the countriesthat apply the taxation system. Ongoing reforms in government taxation which includesthe formulation and manufacture of legislation and improvement of tax administrationthat facilitate services for the taxpayer. The question, after all this time self-assessmentsystem is running, why the level of compliance has not yet reached the optimum level?What drives someone to be obedient and disobedient?This study using convenience sampling method with a sample of 225 respondentsindividual taxpayer listed on STO Pamekasan.The results showed there are significant variable level of education and incomelevel of the Compliance Tax. SPSS test results, that after the simultaneous analysis ofindependent variables significantly influence the dependent variable at the level of 5%(0.05). R Square = 0.154 showed 15% variation Tax Compliance influenced by educationlevel variables and variable rate income and the rest influenced by other factors notknown to include error. With a significance level of 5%, the variable X whichsignificantly affect the Y variable is the variable X1 only to Education for sign value<0.05 while the variable rate income> 0.05